Synergistic Effects of Artemisia vulgaris, Ocimum tenuiflorum, Azadirachta indica and Castanopsis indica Extracts against Methicillin-Resistant Staphylococcus aureus - Chhetri, Jyoti; Gurung, Krishna; Khadka, Abhisek; Sharma, Reeju; Khatri, Mira Kumari; Bhujel, Anil; Acharaya, Amrita; Pokharel, Goma (Himalayan Biodiversity, 2017)
Staphylococcus aureus is a major public health concern. Methicillin resistant Staphylococcus aureus is not only resistant to methicillin and other β-lactam antibacterial agents but also to other antibacterial agents. Therefore, new agents are needed to treat Methicillin Resistant Staphylococcus aureus (MRSA). The main aim of the present research was to study the antibacterial activity of four plants extract against clinical isolates of Staphylococcus aureus at the purpose of overcoming its infection. The current investigation was carried out at Pokhara Bigyan tatha Prabidhi Campus based on the evaluation of traditional plants on its antibacterial activity against MRSA. Antibacterial activity of the medicinal plant extract was observed by mixing 100 g powder of collected leaves in 70% methanol making 1000 sml. After performed processes, extract was filtered and methanol was evaporated. Antibacterial activity of the medicinal plant extract was determined using agar well diffusion assay method. Methanol leaf extracts may have the potential to act against MRSA and could be a possible source to obtain new and effective herbal medicines to treat infections caused by methicillin resistant strains of microorganisms from community as well as hospital settings. The synergistic effect was clearly observed among all four medicinal herbs.